QoS improvement for interactive multi-media traffic under high speed wireless campus network - Yalli, Jameel Shehu (Kulliyyah of Engineering, International Islamic University Malaysia, 2015)
The internet has brought revolution in the telecommunication system. The use of many applications has changed with ease and low cost. Interactive Multi-media (IMM) applications such as Voice over Internet Protocol (VoIP) and Video conferencing are being produced. They offer useful services that benefit academicians, officers and users. But these services suffer performance degradation in the today's high speed Wireless Local Area Network (WLAN). The high speed Wireless Campus Network (WCN) is one which transmits huge traffic in its channel. However, guaranteed Quality of Service (QoS) remains the bottleneck in the network which becomes a great challenge to improve. This work reviewed and presented many approaches attempted to improve the QoS of these applications. The QoS class parameter (i.e Quality of Service Class Identifier-to-Differentiated Services Code Points (QCI/DSCP)) is mapped to the upstream and downstream data flowing in the core of the network. By this, it improves the overall performance of the network. This is achieved by mapping QCI to DSCP and then mapping again the QCI/DSCP to the IMM traffic. This gives highest priority and a strong signal to the QoS bearer packets. The results obtained after simulation in QualNet 5.1 shows that our proposed mechanism gives better performance of the network in comparison to the benchmark. This is measured in terms of three network performance metrics (average delay, average jitter and throughput). The overall average end-to-end delay is decreased by 51.6%, while overall average jitter drops by 32% and the throughput rises slightly by 4.8%.